1982
DOI: 10.1113/jphysiol.1982.sp014454
|View full text |Cite
|
Sign up to set email alerts
|

Relaxing and metabolic inhibitory action of X537A (Lasalocid) on the taenia of the guinea‐pig caecum.

Abstract: SUMMARY1. In the isolated guinea-pig taenia, application of X537A to the muscle caused a relaxation, while A23187 caused a sustained contraction.2. Treatment with adrenergic blocking agents and tetrodotoxin had no effect on the relaxing response to X537A.3. In the presence of a low concentration (10-6 M) of X537A or under hypoxic conditions (bubbled with 95 % N2: 5 % C02), the taenia lost the ability to respond to a high concentration (40 mM) of potassium with a sustained tonic contraction, although the rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…This is indicated by the studies which demonstrate that in the presence of anoxia, both the peak response to bethanechol and the intracellular concentration of ATP decrease over the same time course. These results are similar to those reported by Ishida and Shibata [1982] and Ishida et al [1984] on guinea-pig taenia of the caecum. These investigators demonstrated that the sustained effect of KC1 was lost during hypoxia, whereas the magnitude of the initial phasic contraction decreased in proportion to the concentration of intracellular ATP.…”
Section: Discussionsupporting
confidence: 95%
“…This is indicated by the studies which demonstrate that in the presence of anoxia, both the peak response to bethanechol and the intracellular concentration of ATP decrease over the same time course. These results are similar to those reported by Ishida and Shibata [1982] and Ishida et al [1984] on guinea-pig taenia of the caecum. These investigators demonstrated that the sustained effect of KC1 was lost during hypoxia, whereas the magnitude of the initial phasic contraction decreased in proportion to the concentration of intracellular ATP.…”
Section: Discussionsupporting
confidence: 95%
“…Tissue extracts were made by homogenizing with 6% perchloric acid solution after freezing , or by boiling (Ishida & Shibata, 1982). The smooth muscle tissue (100-150 mg) was incubated in 'normal' solution (see Solutions and chemicals) for 1 h before extraction.…”
Section: High-pressure Liquid Chromatographymentioning
confidence: 99%
“…Substitution of Cl by other anions like Br, NO3, I or SCN potentiates the K-induced initial transient contraction, whereas the same substitution inhibits the following sustained contraction (Urakawa et al, 1967). Only an initial transient contraction is induced by high K (and also by carbachol) in the presence of Ca antagonists like verapamil (Riemer et al, 1974;Karaki et al, 1984), D600 (Brading & Sneddon, 1980), ruthenium red (Kawamura & Yabu, 1978), cyproheptadine (Lowe et al, 1981) and N2-dansyl-L-arginine-4-t-butylpiperidine amide (TI 233) (Karaki et al, 1983c), inhibitors of aerobic metabolism (Pfaffman et al, 1965;Ferrari & Carpenedo, 1968 ;Tsuda et al, 1977;Nakagawa et al, 1984), inhibitors of the Na pump like ouabain (Pfaffman et al, 1965;Kishimoto & Urakawa, 1982a), Li substitution for Na (Pfaffman et al, 1965;Kishimoto & Urakawa, 1982a), and ionophores with mitochondrial inhibiting action like monensin and X-537A (Ishida & Shibata, 1982;Murakami et al, 1983). The initial transient contraction induced by high K in taenia coli coinsides with a burst of spike discharges (Shimo & Holland, 1966).…”
Section: Initial Transient and Following Sustained Contractionsmentioning
confidence: 99%